2019
DOI: 10.21873/anticanres.13440
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Hematological Inflammatory Markers in Predicting Severe Side-effects from Induction Chemotherapy in Head and Neck Cancer Patients

Abstract: Background: Induction chemotherapy (IC) for head and neck cancer (HNC) often causes severe sideeffects. However, it has still been challenging to predict the adverse events. The present study aimed to evaluate the role of hematological inflammatory markers in predicting severe side-effects caused by IC. Materials and Methods: A total of 54 HNC patients who underwent IC were enrolled. The association between severe side-effects and pre-treatment hematological inflammatory markers [the C-reactive protein (CRP) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…The IBPS (NLR, PLR, CAR, GPS, eosinophil count) is a score calculated using the lymphocytes and eosinophils involved in tumor suppression and the neutrophils and platelets involved in tumor growth (28)(29)(30)(31), either on their own or in combination. IBPS is an easily available and non-invasive prognostic biomarker, and is now widely recognized as a new prognostic biomarker for head and neck cancer as well (9)(10)(11)(12)(13)(14)(15)(16)(32)(33)(34)(35)(36)(37). Despite the benefits, most studies have only explored the relationship between the pre-treatment IBPS and the prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IBPS (NLR, PLR, CAR, GPS, eosinophil count) is a score calculated using the lymphocytes and eosinophils involved in tumor suppression and the neutrophils and platelets involved in tumor growth (28)(29)(30)(31), either on their own or in combination. IBPS is an easily available and non-invasive prognostic biomarker, and is now widely recognized as a new prognostic biomarker for head and neck cancer as well (9)(10)(11)(12)(13)(14)(15)(16)(32)(33)(34)(35)(36)(37). Despite the benefits, most studies have only explored the relationship between the pre-treatment IBPS and the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding measuring the IBPS prior to the anticancer drug therapy, Crumley et al have reported that, specifically for GPS, it positively correlated with the frequency of side effects in patients with gastroesophageal cancer (41). IBPS may, thus, be useful for predicting the onset of AEs (36,41). However, unlike other anti-cancer therapies, the occurrence of adverse events in patients treated with ICIs has been shown to be related to a good prognosis (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Several hematological in ammatory markers, such as the C-reactive protein-to-albumin ratio, modi ed Glasgow Prognostic Score, neutrophil to lymphocyte ratio, and platelet-to-lymphocyte ratio, have been used to predict IC toxicity in HNC [11]. The plausible mechanism for the toxicity is attributed to poor nutrition, in ammation, and immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have reported that inflammatory, nutritional, and immune markers were useful for predicting the prognosis [7][8][9][10][11][12][13][14][15] and adverse effects due to chemotherapy 16,17 in various cancers. These markers include C-reactive protein (CRP), Glasgow prognostic score (GPS), 9,10 modified GPS (mGPS), 11,16 neutrophil-tolymphocyte ratio (NLR), 12 platelet-to-lymphocyte ratio (PLR), 13 CRP-to-albumin ratio (CAR), 16,17 and lymphocyteto-monocyte ratio (LMR).…”
Section: Introductionmentioning
confidence: 99%